HYPOVITAMINOSIS D IN HIV-INFECTED PATIENTS - Poiana, C. (Acta Endocrinol (Buchar), 2019)
INTRODUCTION: Vitamin D (VD) deficiency is highly prevalent worldwide. AIM: To assess the prevalence of hypovitaminosis D in HIV-positive Romanian patients compared to controls. METHODS: Serum 25OHD concentration was measured in HIV-infected patients and a control sample, matched by age, sex and menopausal status. The 25OHD status was defined as: deficiency < 20 ng/mL (severe deficiency <10 ng/mL), insufficiency 20-30 ng/mL, normal >30 ng/mL. RESULTS: We evaluated 118 HIV-positive patients (72 males, 46 females), aged 36.9±12.2 years. 98.14% of them were on complex antiviral regimens. The B/C hepatitis coinfection rate was 9.3%. The control sample consisted of 119 subjects, (74 males, 45 women). The median and interquartile range for serum 25OHD concentration in patients was 17.6 (9.7, 26.9) ng/mL and 23.7 (18.4, 27.5) ng/mL in controls (p=0.001). Only 15.96% of HIV-positive cases and 12.71% of controls had normal VD status. The percentage of cases with severe VD deficiency was significantly higher in HIV positive cases (23.52%) compared to HIV-negative controls (4.2%, p=0.001). CONCLUSIONS: Hypovitaminosis D was identified in 84.04% of HIV-infected patients, but the serum 25OHD concentration was not associated with specific HIV-related factors in our sample. Clinical guidelines regarding VD status determination and supplementation in HIV patients are needed.